Effect of Concrete Compression through Mixture of Natural Water - Tunlayapong, Sutee; Maseng, Arong; Thepphrom, Theera; Suyee, Muhammad; Yusoh, Ampandee (Princess of Naradhiwas University Journal, 2021)
This research aimed to study the effect of concrete compressive strength using natural water sources as a mixture. The result was used to compare the compressive strength of concrete using water from Provincial Waterworks Authority as a mixture. The test of compressive strength was done with cylindrical specimens of Ø-15 and 30 cm. in height. The water sources mixed were from 5 natural water sources; the Bang Nara river, Yagang canal, artesian wells, shallow wells and provincial water supply. The results of the concrete compression test at 200 ksc curing period of 28 days showed that the average compressive strength of concrete mixing with natural water sources was 252 ksc. The average of concrete compressive strength of tap water was equal to 271 ksc, and the compressive strength decreased by 7 percent. Comparing with the compressive strength that used a mixture of tap water with a concrete compressive strength at 250 ksc, curing period of 28 days, the average compressive strength of water from natural sources was equal to 291 ksc. The average concrete compressive strength with a mixture of tap water was equal to 303 ksc, and the compressive strength decreased by 4.04 percent. Comparing with the compressive strength that used a mixture from tap water with a concrete compressive strength at 300 ksc, curing period of 28 days, the average compressive strength of concrete mixing with natural water sources was equal to 330 ksc. The average concrete compressive strength with a mixture of tap water was equal to 331 ksc, and the compressive strength decreased by 0.30 percent compared to the compressive strength for a concrete mixture with tap water.